Enhancing motivation, soft skills and perceived learning in accounting using game-based approach - Mat Norwani, Norlia; Ismail, Zuriadah; Yusof, Rohaila; Mohd Nasir, Nastasya Athira; Ahmad, Anis Suriati (Journal of Education and Learning (EduLearn), 2025)
Employers often perceive accounting graduates as lacking motivation and soft skills. The research proposes that game-based learning (GBL) will enhance students' motivation, teamwork, critical thinking, communication skills, and promote learning. Research instruments include academic motivation scale (AMS) utilized to measure motivation, skills assessment scale (SAS) for soft skills, and a test instrument for perceived learning. GBL kit and instruments were validated by experts in accounting. All the research instruments are fit for use with Cronbach Alpha values above 0.9. Using a quasi-experimental design, before the experimental phase, both experimental and control groups did a pre-test for perceived learning. Upon completion of the experimental phase, they did a post-test and answered the AMS and SAS instruments. Regression analyses show that GBL contributed positively and significantly toward the experimental group’s intrinsic and extrinsic motivations and teamwork, critical thinking, and communication skills development. An independent t-test on post-tests shows that the experimental group outperforms the control group. Hence, this study concludes that GBL strategy can create a value-added experience that reinforces learning and enhances competencies. Thus, GBL should be an option in accounting teaching as the benefits achieved are from multiple learning dimensions.